The Drunken Plagiarists. - Neville-Neil, George V. (Communications of the ACM, 2025)
The article discusses tools based on artificial intelligence (AI) and large language models (LLMs) that are designed to aid software developers in their work, referred to as co-pilots. The author explains how LLMs work by drawing on a large amount of Internet content and expresses the view that LLM-based tools do not offer much of value to the process of writing software. He distinguishes between syntactic and semantic elements of software code and says that LLM-based tools can help with syntax but not at all with producing semantically correct or useful code.